MORPHOMETRIC VARIATION OF RATTUS PRAETOR (THOMAS, 1888) COMPLEX FROM PAPUA, WITH THE DESCRIPTION OF NEW SPECIES OF RATTUS FROM GAG ISLAND - Ibnu Maryanto; M. H Sinaga; A. S Achmadi; Maharadatunkamsi (BRIN Publishing (Penerbit BRIN), 2010)
Thirty specimens of Rattus collected from Gag Island, Papua were compareddirectly with two specimens from Gebe Island, one from Salawati Island and sixspecimens from mainland of Papua. All cranial, dental, dentary and external characterswere measured and analysed using multiple regression and discriminant function.The multiple regression showed that only incisive foramina length was influenced bysexual dimorphism. Discriminant function analysis indicated that the form from Gagisland was different from the other populations collected from mainland of Papua,Gebe and Salawati, and thus was described as Rattus nikenii sp. nov.